Pengaruh Kualitas Layanan, Persepsi Harga Dan Lokasi Terhadap Kepuasan Pelanggan Di Cliq Plus Semarang - Muti Mutia; Euis Soliha (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Customer satisfaction is an important element in improving marketing performance in a business. Satisfaction felt by customers can increase the intensity of buying from these customers. This study aims to analyze the effect of service quality, perceived price and location on customer satisfaction at cliq plus Semarang. To determine the sampling of a predetermined population calculated using the Cochran formula. The data collection technique used in this study uses a questionnaire. In the use of questionnaires, measuring respondents' perceptions using 5 Likert scale. Data analysis using the SPSS program. The results showed that service quality has a positive effect on customer satisfaction, price perception has a positive effect on customer satisfaction and location has a positive effect on customer satisfaction. The results of the coefficient of determination test prove that the variables of Service Quality, Perceived Price and Location can contribute to changes in customer satisfaction by 53% and the remaining 47% are influenced by other variables outside the research.